Exploration of the effect of small sided games on the technical skills, internal and external loads of main and joker players - KIZILET, ALİ; BOZDOĞAN, TUBA (MATTIOLI 1885, 2021)
Introduction: The aim of the study is to explore the impact of main and joker players on technical skill responses and internal and external load levels in SSGs. Methods: The participants of the study are 8 elite U17 players who plays in the academy of a professional team training regularly at least five days a week. The height of the participants is 178,9 +/- 3,2cm, the body mass is 71,6 +/- 4,6 kg and body mass index is 20,01 +/- 1,03 kg/m'. SSGs have been performed in a 15x25 meters field, without jokers (3x3), with 1 joker (3x3+1j) and with 2 jokers (3x3+2j). While analyzing data, as a conclusion of test of normality; for the group of 2 Independent Group T-Test or Mann Whitney U test; for the groups of 3 or more ANOVA or Kruskal Wallis H Test have been performed. The significance level has been evaluated as p<0,05. Results: There was no statistically significant difference among HR, HRmax, HRmax% levels of the players (p>0,05). Significant difference was detected in 2 joker games (3x3+2j) in total distance, distance/minute, maximum speed and high intensity running distances of the main players (p<0,05). It is determined that the lactate level and rate of perceived exertion of main players were significantly higher compared to joker players (p<0,05). Conclusions: At the end of the study, it was observed that the use of joker players which provides numerical inferiority/superiority in SSGs effects internal and external load responses of both main and joker players while making the games more fastmoving.
Keywords: soccer; small sided games; game with joker; technical skill; internal and external load; TIME-MOTION CHARACTERISTICS; PHYSIOLOGICAL-RESPONSES; HEART-RATE; SOCCER PLAYERS; DECISION-MAKING; DEMANDS; PERFORMANCE; INTENSITY; NUMBER